EFFECT ON GENE EXPRESSION PROFILE OF HNRNPK KNOCKDOWN IN MOUSE GC-1SPG CELLS - H. Xu; Q. Han; Y. Wang; N. Chen; X. Cheng; S. Yu; C. Li; P. Zhang; Y. Xu (Journal of Animal and Plant Sciences, 2022)
HnRNPK is a multifunctional RNA binding protein. Our previous studies have found that it plays a key role in the survival of spermatogonia GC-1spg, but the mechanism is not clear. To reveal the functional mechanism of hnRNPK in spermatogonia, the expression profiles of hnRNPK knockdown and control groupGC-1spg cells were analyzed by RNA-seq. A total of 1453 differentially expressed genes were obtained, of which 604 genes were up-regulated and 849 genes were down-regulated in GC-1spg cells after hnRNPK knockdown. 24 genes were randomly selected from the differentially expressed genes for qRT-PCR verification. Pearson correlation analysis showed that r = 0.916 (P < 0.01), which indicated that there was a good correlation between the results of RNA-Seq and qRT-PCR. GO functional enrichment analysis showed that the biological process of differentially expressed genes was mainly related to cell proliferation, differentiation, apoptosis and other life activities, and then 17 genes related to proliferation and apoptosis were selected for further verification. The results showed that hnRNPK could affect the survival of GC-1spg cells by regulating proliferation and apoptosis-related genes. KEGG pathways enrichment analysis showed that GC-1spg cells mainly occurred cell-molecule interaction and activation of related signal transduction pathway after hnRNPK knockdown. The results will provide an important basis and clue for revealing the key targets and molecular regulation mechanism in the process of spermatogonia survival, and also provide new ideas to understand the problem of male sterility.
Keywords: Spermatogenesis; Spermatogonia; hnRNPK; RNAi; RNA-Seq